Hollow Mesoporous Carbon Spheres for High Performance Symmetrical and Aqueous Zinc-Ion Hybrid Supercapacitor - Chen, Sihan; Yang, Gaoqi; Zhao, Xiaojuan; Wang, Nengze; Luo, Tingting; Chen, Xu; Wu, Tianci; Jiang, Shijie; van Aken, Peter A.; Qu, Shile; Li, Tao; Du, Liang; et al. (Frontiers in Chemistry, 2020)
Zinc–ion hybrid supercapacitors emerge as promising energy storage devices, by simultaneously combining merits from a high capacity of batteries and a high power of supercapacitors. However, its practical application is hindered by insufficient energy density and poor rate performance. Herein, a symmetrical zinc–ion hybrid supercapacitor device has been constructed with hollow mesoporous-carbon nanospheres as electrode materials, and aqueous ZnSO4 is adopted as electrolyte. Benefiting from the mesoporous structure and high specific area (800 m2/g) of the hollow carbon nanospheres, fast capacitor-type ion adsorption/de-adsorption on both the cathode and the anode can be achieved, as well as additional battery-type Zn/Zn2+ electroplating/stripping on the anode. Thus, the device demonstrates outstanding electrochemical performances, such as a high capacity (212.1 F/g at 0.2 A/g), a high energy density (75.4 Wh/kg at 0.16 kW/kg), a good rate performance (34.2 Wh/kg energy density maintained at high power density of 16.0 kW/kg) and an excellent cycling stability with 99.4% capacitance retention after 2500 cycles at 2 A/g. This work provides a new device engineering configuration for extremely safe, high–rate and durable energy-storage devices.